Konsep Penanggulangan HIV dan AIDS dalam Perspektif Pendidikan Islam - A. Fatoni; Deni Lesmana; Dwi Wulan Sari (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
HIV and AIDS are sexually transmitted infections that are ranked as the big five deadliest diseases in the world. One of the causes of this disease is dangerous sexual intercourse. The type of research used is library research. Library research is research that uses methods to obtain data information by placing existing facilities in the library (such as books, magazines, documents, historical story notes). The approach used in this research is historical-philosophical. The data obtained were analyzed by content analysis. According to the concept of overcoming HIV and AIDS, it can be concluded that a person living with requires treatment with a bio-psycho-socio-spiritual approach to therapy. Education is considered the most strategic aspect in conveying the concept of  HIV and AIDS through responsive learning with a material approach. In the material aspect, there are materials in Islamic education that have a correlation with the concept of HIV and AIDS prevention, such as: Tawhid, Morals, Al-Qur'an Hadith and Fiqh. Aspects of the method, there are methods in Islamic education that can be used in the application of  BPSS theory such as: Interest therapy methods, training and practice, discussions, outbound, Ibrah. Aspects of the goals of Islamic education have relevance to the concept of HIV and AIDS prevention, namely they both want to realize Khoirunnas Anfauhum Linnas